Incorporating Augmented Reality into Natural Science Study for 3rd Grade Elementary School Students - Ayu Savitri, Nadia; Komala Sari, Siska; Hidayat, Wahyu (International Journal of Engineering and Technology, 2019)
Augmented Reality is a technology that construct an interface in which 3D virtual objects are apparently put into the real world. Now research about Augmented Reality are growing rapidly. Utilizing Augmented Reality to improve learning and increase knowledge is one way to increase students' interest in learning. In our research, an augmented reality application is built using Blender, Unity and Vuvoria through ADDIE analysis and design model. This application is intended to facilitate teachers and students in teaching and learning Natural Science for 3rd grade elementary school, more specifically in â€œPlant and Animal Introductionâ€ chapter. By scanning the marker on the book, this application is capable of displaying animated 3D objects that can be viewed from all sides. This application also features real-life-like animal-sound and facilitate object zoom in - zoom out. Our test shows that this application is welcomed by students and teachers alike and as a supplement to enhance Natural Science Study learning experience.Â Â